PRODUCTION OF RECOMBINANT MILK-CONVERTING ENZYME IN YEAST PICHIA PASTORIS - Akishev , Zh.; Auyez , M.; Baltin, K.; Tursunbekova , A.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2024)
Chymosin is the main enzyme with a high degree of specificity towards k-casein and is therefore used in the cheese industry. This work presents the results on the expression of the goat prochymosin gene in the yeast Pichia pastoris and the study of the milk-clotting activity of recombinant goat chymosin. The goat prochymosin gene was integrated into the chromosomal DNA of yeast and the secretion of prochymosin into yeast culture was carried out by methanol induction. After activation, chymosin was purified by sequential anion and cation exchange chromatography. A biochemical study showed that a decrease in the milk-clotting activity of the enzyme was observed with an increase in pH. The highest activity of recombinant goat chymosin was manifested at 60 °C and pH 4.5-5.0 and amounted to 7680 ± 0.32 and 8727 ± 0.39 for cow's and goat's milk, respectively. The total proteolytic activity of the enzyme was 7769.2±0.38 U/mg. The results obtained suggest that recombinant goat chymosin can be used in the cheese industry and has good prospects for practical application in the production of cheese from goat's milk.